Pembelajaran Kelembagaan Nasional dan Internasional untuk Penguatan Tata Kelola Lingkungan melalui Teori Bedah Jantung - Simanjuntak, Hengki; Rusdi; Sudarmanto, Arif (Jurnal Ilmu Ilmu Kehutanan, 2025)
The Heart Surgery Theory emerges from the ongoing governance crisis in Indonesia's environmental sector, characterized by institutional fragmentation and sectoral disconnection. This theory proposes a collaborative governance approach that emphasizes spatial and temporal synchronization combined with the application of mutual accountability across sectors. The Cantelan mechanism anchors budgetary allocations (DIPA/DPA) to specific priority locations, ensuring the simultaneous presence of forestry, environment, public works, agriculture, and social sectors in critical ecosystems. This study applies a reflective literature review combined with lessons from national and international practices, including TVA (United States), MDBA (Australia), and ICPR (Europe). The results indicate that spatial-temporal locking and mutual accountability reduce bureaucratic inefficiencies, close governance loopholes, and strengthen bureaucratic integrity in ecosystem restoration efforts.